Efektivitas Kalsium Hidroksida sebagai Bahan Obturasi Pulpektomi Pada Gigi Desidui - Pristika, Aena; Nurnaini, Lasmi Dwi (Jurnal Material Kedokteran Gigi, 2023)
Pulpectomy is a conservative treatment approach for caries that has reached the pulp, chronic inflammation, or pulp necrosis. There are several materials for root canal obturation in deciduous teeth, namely calcium hydroxide, zinc oxide eugenol (ZOE), and iodoform paste mixed with calcium hydroxide. Calcium hydroxide is a root canal obturation material that has the effect of inhibiting macrophage phagocytosis so that it can reduce the inflammatory reaction. Objective, to describe the effectiveness of calcium hydroxide as an obturation material for pulpectomy treatment. Research methods, literature review, sources collected through the PubMed, Science Direct, Google scholar and ResearchGate databases. The criteria used are articles from 2020-2025 that can be fully accessed. Based on the findings of the three articles discussed above, it can be concluded that calcium hydroxide is an effective material for use as a root canal filling material. One of the effective materials used as a root canal filling material is calcium hydroxide. The properties of calcium hydroxide are antibacterial properties, healing properties, and the ability to be reabsorbed if used excessively and its biocompatible properties.